Ekspresi MMP-9 dan TIMP-1 pada Ameloblastoma tipe Folikular, Pleksiform dan Akantomatosa - , SELVIANA WATI FOBIA, Drg. Prihartiningsih, SU., Sp. BM (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ameloblastoma is a common odontogenic tumor located in jaws, and is considered as a benign but agressive and locally invasive, which is difficult to treat and cause morbidity. Many histolopathological variant of ameloblastoma. Pleksiform type, folikular type and acanthomatous type are the most common, and each has potensial to become more agressive than others. Matrix metalloproteinase-9 (MMP-9) and Tissue inhibitor of metalloproteinase-1 (TIMP- 1) are proteinases that participate in extracellular matrix(ECM) degradation, influencing the aggresivity. The aim of study is to make an observation of the balance between MMP-9 and TIMP-1(MMP-9 inhibitor)in three different histopathological type of ameloblastoma. All the subject are derrived from laboratorium of pathology Dr. Sardjito Hospital, in form of parafin block of ameloblastoma, from oral surgeryâs patients, Dr. Sardjito Hospital, Yogyakarta, in year 2008-2012. Three main histopathological type will be the subjects, each subjects will be stained by HE, MMP-9 and TIMP-1, and the immunoscore will be taken to compare the expressions that describe the agressivity. Both protein MMP-9 and TIMP-1 were detected in all 28 (77,8%) subjects of ameloblastoma